Encapsulation of carvacrol, a monoterpene present in the essential oil of oregano, with ß-cyclodextrin, improves the pharmacological response on cancer pain experimental protocols. - Guimarães, Adriana Gibara (2015)
Federal University of Sergipe. Department of Health Education. Lagarto, SE, Brasil